Multicentre, Prospective Observational Study of Pegfilgrastim Primary Prophylaxis in Patients at High Risk of Febrile Neutropenia in Poland: PROFIL Study - Jurczak, Wojciech; Kalinka-Warzocha, Ewa; Chmielowska, Ewa; Duchnowska, Renata; Wojciechowska-Lampka, Elzbieta; Wieruszewska, Karolina (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : PROFIL was a prospective observational study conducted to investigate physicians’ evaluation of febrile neutropenia (FN) risk and reasons for giving pegfilgrastim primary prophylaxis (PP) in routine clinical practice in Poland. Material and methods : Adult cancer patients treated with chemotherapy (CT), assessed by investigators as having high overall FN risk, and who received pegfilgrastim in cycle 1 were enrolled between 03/2009 and 09/2010. Investigators assessed FN risk of the CT regimen, individual risk factors, and overall FN risk, and were asked to provide the most important reasons for providing pegfilgrastim PP. Investigator-assessed CT FN risk was compared with guideline classification. Results : Data were analysed from 1006 breast, ovarian, and lung cancer, and non-Hodgkin (NHL) and Hodgkin lymphoma (HL) patients. The most important reasons for using pegfilgrastim PP were high CT FN risk and advanced disease; these were consistent across tumour types and treatment intent. The investigators generally assessed high CT FN risk in agreement with guideline classification. Febrile neutropenia occurred in 4% of patients, most commonly in HL, NHL, and patients with advanced disease. Conclusions : High CT FN risk and advanced stage of disease were found to be the most important reasons for providing pegfilgrastim PP by physicians in Poland.